Ozaaweshiinh Ləkʷəŋən/W̱SÁNEĆ-aking: An Ojibwe Language and Culture Needs Assessment in Victoria B.C. - Craig, Carmen Wiigwaas (2023)
This multi-method project explores the language learning needs, wants, and responsibilities of the urban Ojibwe (Anishinaabe, Nishnaabe) community currently living in Ləkʷəŋən and W̱SÁNEĆ territories (Victoria, British Columbia). The purpose of this research is to discover what is needed and wanted in order to rebuild the Ojibwe language (Ojibwemowin, Nishnaabemwin, Anishinaabemowin) relationship for the urban Ojibwe community living on these territories. The study employed a survey, a talking circle, and an interview with a local language practitioner to gather knowledge. In sharing their dibaajimowinan, or stories in circle or through survey or interview, participants identified various responsibilities and strengths of the community, including learning and using some basic phrases/place names in SENĆOŦEN or Ləkʷəŋən languages and that the community provides a strong and important sense of safety, belonging, connection, and affirming of identity for people who are a part of it. Participants also shared their needs and wants for support, people, spaces, and opportunities to gather, as well as their goals related to speaking, understanding, reading, and writing Ojibwemowin. However, they also identified barriers to their language and culture learning, such as living far away from traditional territories, not having access to structured learning, feeling conflicted about learning on this territory, and having emotional and/or confidence issues related to learning. Overall, the findings of this project highlight the importance of investing in safe and supportive spaces, offering diverse and accessible language and culture learning opportunities that address the identified needs and barriers, and supporting the ongoing efforts for urban Ojibwe people to reclaim their language and culture whether near or faraway from homelands. Graduate